Cover Image, Volume 176A, Number 9, September 2018. Issue 9 (22nd September 2018) - Burren, Christine P.; Caswell, Richard; Castle, Bruce; Welch, C. Ross; Hilliard, Tom N.; Smithson, Sarah F.; Ellard, Sian
Abstract : The cover image, by Christine P. Burren et al., is based on the New Syndrome TRPV6 compound heterozygous variants result in impaired placental calcium transport and severe undermineralization and dysplasia of the fetal skeleton, DOI: 10.1002/ajmg.a.40484 .